Serial Storytelling: A Therapeutic Approach with a Young Adolescent - Allan, John A. B. (Canadian Journal of Counselling and Psychotherapy, 2012)
A seventh grade teacher consulted the school counsellor regarding a boy with learning problems who wrote violent stories in the creative writing class. The teacher was concerned that the boy might begin to act out his murderous fantasies. Based on an aspect of Jung's ( 1966) theory that psychological growth occurs when fantasies are expressed through a creative medium (i.e., painting or writing) serial storytelling was used as therapeutic technique. In this method, the boy wrote the stories for the teacher who in turn brought them to the counsellor for further discussion and understanding. In all, sixteen stories were gathered over a thirty-two week period.The stories dealt with themes of separation, the struggle between dependency andindependency, envy, rage, mystery, the development of a conscience and the emergence of a new identity. The boy's school work improved and follow-up one anda half years later indicated that he was making good progress in grade nine.